Entrepreneurial support for startups: A systematic literature review using the PRISMA method - TAMOUH, Nadia; JABRI, Nour-elhouda; LAHRACH, Rahhal; ASRAR, Wissal (Revue Internationale des Sciences de Gestion, 2025)
Despite their potential for economic redefinition, many start-ups face challenges and failures. Thus, tailored entrepreneurial support is indispensable. This article aims to present a systematic review on the evolution of entrepreneurial support for start-ups, using the PRISMA method to identify and synthesize scientific articles. The objective is to explore the role of entrepreneurial support in the success of innovative enterprises. The research method involved selecting databases such as Science Direct, Web Of Science, Springer, Scopus, Jstor, Cairn.info, Google Scholar, with keywords in both French and English such as "AE," "Start-ups," "entrepreneurial support." Selection criteria included language (English and French), publication date (2000-2024), covering both foundational and recent works. The results of 69 articles studied highlight that support for start-ups contributes to their success and sustainability. Different theoretical approaches to entrepreneurial support and its impact on start-up continuity were examined. This analysis demonstrated the importance of support structures tailored to the varied profiles of entrepreneurs. In conclusion, the article highlights the essential link between entrepreneurial support and start-up success, thus offering valuable insights for practitioners and researchers in this field.